2018
DOI: 10.1111/jcpe.12857
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive approach to assigning periodontal prognosis

Abstract: AimThe purpose of this retrospective case series study was to evaluate the usefulness and performance of a comprehensive approach to assigning periodontal prognosis by assessing the risk of tooth loss due to periodontal disease (TLPD) and estimate the survival time (ST) of periodontally compromised teeth (PCT).Material and MethodsThe Long‐Term Outcome (LTO) index was utilized to assess the risk of TLPD, at baseline, in 100 patients following periodontal maintenance for a mean 24.7 year (±2.4). A TLPD predictio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Overall, 9 studies showed high ROB related to outcomes, with some of them being suspected to multiple biases. Of the 34 identified studies, 3 did not use a prespecified or clear outcome definition (Prince et al 2016; Su et al 2017; Martinez-Canut and Llobell 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, 9 studies showed high ROB related to outcomes, with some of them being suspected to multiple biases. Of the 34 identified studies, 3 did not use a prespecified or clear outcome definition (Prince et al 2016; Su et al 2017; Martinez-Canut and Llobell 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 16 studies that categorized continuous variables, 12 classified age into 5-y age groups ( n = 7) or larger categories ( n = 5). Three studies categorized pocket probing depth and/or level of bone loss (Martinez-Canut et al 2018; Martinez-Canut and Llobell 2018; Schwendicke et al 2018), and 2 studies categorized laboratory test results, such as low-density lipoprotein (OuYang et al 2017; Peng et al 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Their tooth-prognosis system was associated with tooth loss in a retrospective analysis with at least 5 years of follow-up. Other authors proposed prediction models of tooth loss determined by patient and tooth factors (Avila et al 2009;Martinez-Canut & Llobell, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In regard to periodontal disease, several prognostic tools have been suggested in the literature [5,6]. A commonly used one is the McGuire and Nunn Classification [6].…”
Section: Introductionmentioning
confidence: 99%